Exploring dry grain fractionation as a means to valorize high‐protein malting barley. Issue 4 (4th May 2021) - Izydorczyk, Marta; Nam, Shin; Sharma, Arzoo; Kletke, Jerry
Abstract: Background and objectives: Malting barley cultivars are potentially the most profitable commodities for producers; however, barley selected for malting purposes has to meet many stringent quality requirements. Barley with excessive grain protein concentration (>13%) is often the reason why it is rejected for malting grade and sold at a lower price on the feed market. The objectives of this study were to explore dry grain fractionation as a means to valorize high‐protein malting barley by producing high fiber/protein fractions for human nutrition and starchy fractions for adjunct brewing. Findings: Several malting barley varieties with grain protein concentration above 14% (db) were milled on a Buhler laboratory mill resulting in six flours streams. Coarse and fine shorts were further processed using a Buhler laboratory shorts duster resulting in coarse fiber fractions and two additional flour fractions. The total yield of combined flour fractions ranged from 50.2% to 51.6%, whereas the yield of fiber fractions ranged from 41.5% to 43.7%. The fiber fractions were enriched in β‐glucans (9.3%–11.2%, db), arabinoxylans (9.9%–11.3%, db), and proteins (22%–26%, db) with average 2.2‐, 1.7‐, and 1.5‐fold increase of these constituents, respectively, compared to the whole grain. The content of vitamin E in fiber fractions was higher than in the whole grain, ranging from 82 to 109 ug/g. The fiber fractions also exhibited an improved ratio of tocotrienol to tocopherols. The combined flour fractions were depleted of β‐glucans (0.6%–0.7%, db) and arabinoxylans (0.5%–0.6%, db), contained acceptable levels of proteins (11.5%–13.5%, db) and high levels of starch (79%–82%, db). Mashing experiments with up to 40% replacement of malt with flour fractions showed significant improvements in malt extract without negative influence on malting quality parameters, such as wort beta‐glucans, wort viscosity, and the average degree of polymerization of starch dextrins. Conclusions: The study demonstrated that covered barley can be milled using milling equipment commonly used in wheat milling without the necessity of prior dehulling of the grain. The milling resulted in two high‐yield fractions (flour and fiber/protein‐rich fractions) with hulls effectively separated during the early stages of milling, making the fractionation process commercially feasible. Significance and novelty: High‐protein barley can be valorized by fractionation into fiber/protein‐rich fractions that can be used as valuable food ingredients for the effective and economical control of many food‐related health issues and into starchy flour fractions that can used as adjunct in brewing.